Integrating Information and Communication Technology in the Classroom: - Bastien Sasseville (The Canadian Network for Innovation in Education (CNIE), 2004)
The discourse about information technology is often overlooked by researchers and scholars as a means of understanding the recent process of computerization in education. The research explores this phenomenon through a comparative discourse analysis of primary and secondary school teachers and promoters of ICT integration. The results show that promoters tend to view ICT as a way of transforming education whereas teachers see it only as a means to an end. The former's vision is borrowed from a prospective current of thought, a vision of social changes based on technological advances; the latter's considers only the needs of the students and the practical ways to respond to them. The research shows that teachers are not opposed to ICT integration; they're interested in effective ways to implement learning. The organizational context into which ICT is integrated is also a major impediment when it comes to changing the teacher's practice.